How Humanistic Is Positive Psychology? Lessons in Positive Psychology From Carl Rogers' Person-Centered Approach—It's the Social Environment That Must Change - Joseph, Stephen (Frontiers in Psychology, 2021)
Both positive psychology and the person-centered approach share a common aim to promote human flourishing. In this article I will discuss how the person-centered approach is a form of positive psychology, but positive psychology is not necessarily person-centered. I will show how the person-centered approach offers a distinctive view of human nature that leads the person-centered psychologist to understand that if people are to change, it is not the person that we must try to change but their social environment. Centrally, the paper suggests that respecting the humanistic image of the human being and, consequently, influencing people's social environment to facilitate personal growth would mean a step forward for positive psychology and would promote cross-fertilization between positive psychology and the person-centered approach instead of widening their gap.